Vitamin D Level and Immune Modulation in Children with Recurrent Wheezing - Feketea, Gavriela; Vassilopoulou, Emilia; Andreescu, Oana; Berghea, Elena Camelia; Pop, Raluca Maria; Sabin, Octavia; Zdrenghea, Mihnea; Bocsan, Ioana Corina (Children (Basel), 2024)
Introduction and aim: A direct causal relationship between vitamin D (vit D) deficiency and recurrent wheezing has not been proven. The present study investigated the role of vit D in enhancing the risk of asthma or recurrent wheezing by modifying the intensity of the inflammatory process. Material and method: Forty children with wheezing presenting at the emergency service and sixteen healthy control subjects were included in the study. Children with wheezing were either in the first episode (20) or with recurrent wheezing (20). Children with chronic diseases, and other conditions that present with acute wheezing or that might influence the vit D level, were excluded. Blood samples were taken at presentation and 3–6 months later, to evaluate the serum levels of total IgE, vit D, IL-10 and IL-31. Statistical analysis was performed using the SPSS 25 program, with a significance level of p < 0.05. Results and conclusion. The vit D level was lower in patients with recurrent wheezing compared with those with a single episode and with the control group, and this increased with time. IL-10 was significantly higher in children with wheezing than in the control group, with the highest values in those with an acute episode of wheezing. IL-31 was higher in children with recurrent wheezing than in those with a first episode only at the initial point, while at the final time point it was lower. Low levels of vit D appear to be detected more frequently in recurrent wheezing than in simple wheezing. Immune modulation, as measured by Th2 status reflected by IL-10 and IL-31 levels, appears to depend on the wheezing phenotype and on the general health status.